An exploratory investigation of lipid-lowering potential of spirulina (Arthrospira platensis) targeting apoprotein-E in chronic hyperlipidemic wistar albino rats - Anum Nazir; Mahr Un Nisa; Mohamed H. Mahmoud; Ahmed M. El-Gazzar; Eliasse Zongo (Cogent Food & Agriculture)
Spirulina (Arthrospira platensis) is the most famous species of microalgae and is a possible source of important chemicals and therapeutic metabolites with a variety of pharmacological effects. This study investigated the nutritional profile of spirulina powder and its potential to decrease hyperlipidemia in male Wistar albino rats. The rats were divided into five groups: G1 (spirulina powder 300 mg/kg), G2 (spirulina powder 600 mg/kg), G3 (spirulina powder 900 mg/kg), PC (positive control; no treatment), and NC [negative control + chow rodent diet (CMD)] throughout the experimental period. Blood samples from rats were analyzed for albumin apoprotein-E, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides, and cholesterol levels. Rat liver tissues were examined histopathologically to observe morphological changes before and after the course of treatment. Overall findings demonstrated that in comparison to all other groups except NC, a high dose of spirulina (900 mg/kg) significantly decreased cholesterol levels (68.8 ± 1.4 mg/dl), triglyceride levels (86.7 ± 2.2 mg/dl), and LDL (20 ± 0.82 mg/dl). However, it also significantly increased HDL (46.8 ± 2.46 mg/dl) and apoprotein-E levels (6.13 ± 0.1). Alanine transaminase (ALT) and aspartate aminotransferase (AST) levels were significantly (p ≤ 0.05) reduced in all treatment groups compared to PC, except for NC. In conclusion, spirulina powder is an excellent source to mitigate hyperlipidemia, with promising pharmacological potential in the prevention of chronic diseases.